Gendered Impacts of Environmental Degradation in Informal Settlements: A Comparative Analysis and Policy Implications for India, Bangladesh, and Pakistan - Patel, Amit; Lotia, Hina; Malik, Ammar A.; Mundt, Marcia D.; Lee, Hyunjung; Rafiq, Muhammad Arshed (Journal of Comparative Policy Analysis: Research and Practice, 2020)
Degraded urban environments disproportionately affect marginalized populations, and especially impoverished women in South Asia’s informal settlements, where climate change vulnerabilities and gender inequalities are extreme. A comparative analysis was conducted of three neighboring countries, India, Bangladesh, and Pakistan, where urban environments, climate risks, and gender relations exhibit significant variances. With original survey data from 12 informal settlements across New Delhi, Dhaka, Islamabad, and Lahore, it was found that women are less empowered than men in all three countries, but their determinants related to environmental degradation and climate change vary. Qualitative data from key informants reveals several explanatory mechanisms of observed differences.
KerkoCite.ItemAlsoKnownAs: 5072953:CLQKCPFS 5072953:DFT6J8QC 5072953:LLYAF6N5
Keywords: _z:class:countries; comparative analysis; environmental degradation; informal settlements; mixed methods; women’s empowerment